Influence of cork density on compression - Rodrigues, C. (2013)
The compression properties of cork were studied on samples grouped in three density classes: 0.11 - 0.15, 0.15 - 0.19 and 0.19 - 0.25 g cm3. In all cases, cork had higher strenght for the radial compression. There were significant differences between cork samples with higher density showed overall larger resistance to compression in the three directions.